Enhancement of the Diversity of Pollinators and Beneficial Insects in Intensively Managed Vineyards - Peris-Felipo, Francisco Javier; Santa, Fernando; Aguado, Oscar; Falcó-Garí, José Vicente; Iborra, Alicia; Schade, Michael; Brittain, Claire; Vasileiadis, Vasileios; Miranda-Barroso, Luis (Insects (Basel, Switzerland), 2021)
(1) Modern, intensive agricultural practices have been attributed to the loss of insect biodiversity and abundance in agroecosystems for the last 80 years. The aim of this work is to test whether there are statistically significant differences in insect abundance between different zones and over time on the vineyard field. (2) The study was carried out in five intensive wine farms in Spain over a three-year period (2013–2015). Each field was divided into two zones, one where cover plants were planted, and another remained unchanged (without cover). (3) A clear trend to increase the average number of insect species and individuals throughout the years in all farms was observed. Moreover, the zones with cover plants showed a significant difference with respect to the zones without. (4) The use of permanent cover plants allows creating areas of refuge for the insects favouring their conservation and reducing the agriculture impact in the insect decline.